Understanding civil society before and after 1989 - Miszlivetz, Ferenc (RECERCA. Revista de Pensament i Anàlisi, 2012)
Entrapped in the ambiguities of the Realpolitik of the Yalta system, East and Central European societies had to proceed on a long path of learning in order to find the right modes of self-organization and articulation to defend their values and identities vis-à-vis dictatorship and authoritarian rule. These bitter lessons contributed to the emergence of a new «strategy», a new vision which materialized in the emerging political philosophy and the political and social practice of civil society. This development would not have been possible without a gradual and fundamental change in political thinking and goal-setting, expressed in the development of a new concept of civil society. Atrapados en las ambigüedades de la Realpolitik del sistema de Yalta, las sociedades del Centro y Este de Europea han tenido que proceder a un largo camino de aprendizaje a fin de encontrar formas correctas de autoorganización y la articulación de la defensa de sus valores e identidades vis-à- vis con una dictadura y una administración autoritaria. Estas amargas lecciones contribuyeron a la emergencia de una nueva «estrategia», una nueva visión materializada en la emergente filosofía política y la práctica social y política de la sociedad civil. Este desarrollo no hubiera sido posible sin el gradual y fundamental cambio en el pensamiento político y el establecimiento de metas, expresadas en el desarrollo de un nuevo concepto de sociedad civil.